2012
DOI: 10.1016/s0140-6736(11)61817-5
|View full text |Cite|
|
Sign up to set email alerts
|

A pharmacist-led information technology intervention for medication errors (PINCER): a multicentre, cluster randomised, controlled trial and cost-effectiveness analysis

Abstract: SummaryBackgroundMedication errors are common in primary care and are associated with considerable risk of patient harm. We tested whether a pharmacist-led, information technology-based intervention was more effective than simple feedback in reducing the number of patients at risk of measures related to hazardous prescribing and inadequate blood-test monitoring of medicines 6 months after the intervention.MethodsIn this pragmatic, cluster randomised trial general practices in the UK were stratified by research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
450
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 357 publications
(479 citation statements)
references
References 27 publications
(51 reference statements)
15
450
0
1
Order By: Relevance
“…The eight prescribing safety indicators identified 1435 instances of potentially hazardous prescribing or lack of recommended monitoring in a total population of 92,649 patients. Compared with findings from the PINCER Trial, 21 the proportion of patients identified at risk for each of the prescribing safety indicators was similar or lower, with the exception of the indicator relating to the monitoring of patients receiving warfarin, which was higher.…”
Section: Prescribing Safety Indicatorsmentioning
confidence: 58%
“…The eight prescribing safety indicators identified 1435 instances of potentially hazardous prescribing or lack of recommended monitoring in a total population of 92,649 patients. Compared with findings from the PINCER Trial, 21 the proportion of patients identified at risk for each of the prescribing safety indicators was similar or lower, with the exception of the indicator relating to the monitoring of patients receiving warfarin, which was higher.…”
Section: Prescribing Safety Indicatorsmentioning
confidence: 58%
“…Randomized Controlled Trials where results arising from the testing phase of a specific CDSS are reported without any technical details about the system [8][9][10][11][12] ; 2. Systematic Reviews, which summarize previously published Randomized Controlled Trials and assess the impact and potential of CDSSs in clinical practice 7,13,14 ; 3.…”
Section: Semi-active Systemsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Most of the indicator sets developed specifically for primary care originated in the UK. [12][13][14][15][16][17] Other methods of analysing prescribing also exist, for example, prescribing analysis and cost tabulation (PACT) data and the Medication Appropriateness Index (MAI). 18,19 There are obvious limitations with PACT data because of a lack of linkable clinical information, and the MAI is a time-consuming process involving detailed medical records analysis.…”
Section: Introductionmentioning
confidence: 99%